Producer Gas Cleaning Process From Biomass Gasification And Its Impact On Solid Oxide Fuel Cells Performance - Zia, Ud Din (2018)
Biomass derived producer gas (PG) can be efficiently converted into electricity in solid oxide fuel cells (SOFC) at their operating temperature between 700–900 °C if sufficiently cleaned from PG contaminants especially tar. Amongst the tar cleaning options, thermal cracking offers the advantage of increasing the PG heating value by cracking tar into useful gases and the heat available can be utilized as heat source for SOFC operation. However, current tar thermal cracking systems are at lab–scale and are based on less efficient and expensive electric furnaces. Alternatively, thermal cracking system based on Microwave (MW) heating is rather more efficient and cost effective and has the potential for process scale–up. In this work, a modified industrial MW oven was developed and characterized for tar thermal cracking and integrated with a 10 kWth downdraft gasifier. The sensible heat of PG from MW tar cracking reactor was preserved in a stainless steel (SS) chamber for the operation of a 60 W single SOFC. PG was then subjected to a cooling process prior to compression in a compressor as a further tar cleaning mechanism of biomass tar. Particulates and traces of alkali metals and HCl were removed via cooling and filtration processes. The remaining contaminant H2S was removed using urea impregnated coconut shell activated carbon (CSAC) before feeding the cleaned compressed PG to a SOFC in a thermally insulated stainless steel chamber. The experimental work showed that MW tar cracking reactor converted 95% of particulates and 93% of tar into combustible gases resulting in the highest heating value of 5.53 MJ Nm-3 at 1250 °C. Tar was reduced from 1703 mg Nm-3 to 140 mg Nm-3. Kinetic studies revealed that tar conversion rate was 1.7 times faster under MW heating as compared to conventional heating. The high temperature PG exiting MW reactor of above 800 °C is suitable for SOFC operation thus omitting an electric furnace otherwise required to maintain SOFC operating temperature. The compression of PG in a compressor further reduced tar to 22 mg Nm-3 exhibiting 84% removal efficiency. All PG contaminants were successfully reduced below the probable tolerance limits for SOFC using the designed cleaning system. SOFC exhibited the stable voltage of 0.865 V for the tested duration of 300 min under current density of 260 mA cm-2 without showing any significant degradation under PG operation with low S/C=0.3 but still under thermodynamic carbon deposition free conditions. A single SOFC delivered the power of 23 W with the electrical efficiency of 24% at the low fuel utilization factor of 36%. PG as fuel did not cause any deteriorating effects on anode microstructure. The SOFC exhibited comparable performance under thermal profile sustained by hot PG with those of the cells operated in temperature controlled electric furnaces in similar conditions.